2017
DOI: 10.1016/j.jjcc.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Significance of change in serum bilirubin in predicting left ventricular reverse remodeling and outcomes in heart failure patients with cardiac resynchronization therapy

Abstract: The change in serum bilirubin is useful for assessment of left ventricular reverse remodeling and prediction of outcomes in heart failure patients with CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Hosoda et al (Ref. 35; Table 1) also demonstrated poor prognoses in patients with heart failure with elevated baseline total bilirubin levels before cardiac resynchronization therapy. Furthermore, when 69 patients were divided into groups with increasing or decreasing bilirubin concentrations~5 mo after resynchronization, patients with decreasing total bilirubin levels demonstrated improved end-systolic/diastolic diameters and ejection fraction, with fewer instances of cardiac death and rehospitalization for heart failure over a 39 mo followup.…”
Section: Protection Of the Myocardium From Acute Ischemia-reperfusion Injurymentioning
confidence: 94%
“…Hosoda et al (Ref. 35; Table 1) also demonstrated poor prognoses in patients with heart failure with elevated baseline total bilirubin levels before cardiac resynchronization therapy. Furthermore, when 69 patients were divided into groups with increasing or decreasing bilirubin concentrations~5 mo after resynchronization, patients with decreasing total bilirubin levels demonstrated improved end-systolic/diastolic diameters and ejection fraction, with fewer instances of cardiac death and rehospitalization for heart failure over a 39 mo followup.…”
Section: Protection Of the Myocardium From Acute Ischemia-reperfusion Injurymentioning
confidence: 94%
“…STB levels are associated with a high thrombus burden in STEMI patients [ 28 ]. STB could be elevated in HF patients, and reduced STB could reflect improved end-systolic/diastolic diameters and ejection fraction (EF) after resynchronization therapy [ 29 ]. Elevated bilirubin is also an independent predictor for hypertensive patients [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the proper discretion has to be shown in interpreting the data of blood tests. Intriguingly, it has also been reported that a decreased ratio in serum bilirubin could predict LV reverse remodeling and outcomes in HF patients with CRT [21]. Dutta et al demonstrated that administration of b-3 blocker attenuates peripheral monocytosis and infiltration of monocytes into myocytes in mice with myocardial infarction [3].…”
Section: Discussionmentioning
confidence: 99%